ANALISIS DAN PERANCANGAN APLIKASI PENJUALAN PAKET TRAVEL BERBASIS WEB DENGAN METODE MODEL VIEW CONTROL - Ferdy Santoni; Pastima Simanjuntak (Computer Science and Industrial Engineering, 2025)
In this digital era, the tourism industry is one of the sectors that highly requires technology, such as the use of applications or websites, to remain competitive and reach a broader range of customer seeking tour and travel services. Tourism continues to grow rapidly alongside the increasing public interest in business, educational, or recreational travel. However, several challenges often arise in managing travel package sales, such as difficulties in booking processes due to limited accessibility, inefficient data management and a lack of flexibility in meeting customer needs. A structured system is designed using the Model View Controller (MVC) method to address these issues and meet the needs of both customers and companies effectively.